A study on usage status of electronic payment system (EPS): before, during and after COVID 19 pandemic lockdown period in India - Rengasamy, Dhanuskodi (2020)
COVID-19 pandemic enforces the world to move the electronic payment system. Due to nationwide lockdown in India for the period of 68 days in four phases starting from 25 March and ends on 18 May 2020, most of the payments are through electronic payment system (EPS). For purchases of goods and services through a physical store, where the shops used point of sale (POS) terminals for processing the card payment or a virtual sales point such as a computer, mobile or electronic devices applied electronic payment system. EPS comprises various methods but the present study mainly focuses on card services such as debit and credit cards. It is a quantitative study that classifies the study period into three sectors are before, during, and after the COVID 19 pandemic lockdown period in India. The objective of the research is to study the usage status of debit and credit cards for POS, it includes both numbers of transactions and amount of transactions. Usage status is measured through growth percentage. The study depends on secondary data were collected from RBI publications specifically from Bank wise ATM/POS/Card statistics. Based on data analysis the study concluded that the growth percentage of both debit and credit card usage for POS has been decreased from before the lockdown period to during the lockdown period. After the lockdown period, the status of usage increased in all banks. Overall, the decrease in the growth percentage of usage of cards is between 50% and 70% from before the lockdown period during the lockdown period. At the same time, the growth percentage of card usage has been increased in both number and amount of transactions from during the lockdown period to after the lockdown period is between 55% and 154%